Preemptive interferon-α therapy could prevent relapse of acute myeloid leukemia following allogeneic hematopoietic stem cell transplantation: A real-world analysis - Fan, Shuang; Pan, Tian-Zhong; Dou, Li-Ping; Zhao, Yan-Min; Zhang, Xiao-Hui; Xu, Lan-Ping; Wang, Yu; Huang, Xiao-Jun; Mo, Xiao-Dong (Frontiers in Immunology, 2023)
Measurable residual disease (MRD)-directed interferon-α treatment (i.e. preemptive IFN-α treatment) can eliminate the MRD in patients with acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Therefore, this study aimed to further assess its efficacy in a multicenter retrospective study in a real-world setting. A total of 247 patients who received preemptive IFN-α treatment were recruited from 4 hospitals in China. The protocols for MRD monitoring mainly based on quantitative polymerase chain reaction [qPCR] and multiparameter flow cytometry [MFC]. The median duration of IFN-α treatment was 56 days (range, 1–1211 days). The cumulative incidences of all grades acute graft-versus-host disease (aGVHD), all grades chronic graft-versus-host disease (cGVHD), and severe cGVHD at 3 years after IFN-α therapy were 2.0% (95% confidence interval [CI], 0.3–3.8%), 53.2% (95% CI, 46.8–59.7%), and 6.2% (95% CI, 3.1–9.2%), respectively. The cumulative incidence of achieving MRD negative state at 2 years after IFN-α treatment was 78.2% (95% CI, 72.6–83.7%). The 3-year cumulative incidences of relapse and non-relapse mortality following IFN-α therapy were 20.9% (95% CI, 15.5–26.3%) and 4.9% (95% CI, 2.0–7.7%), respectively. The probabilities of leukemia-free survival and overall survival at 3 years following IFN-α therapy were 76.9% (95% CI, 71.5–82.7%) and 84.2% (95% CI, 78.7–90.1%), respectively. Multivariable analysis showed that MRD positive state by qPCR and MFC before IFN-α treatment, high-risk disease risk index before allo-HSCT, and receiving identical sibling donor HSCT were associated with a higher risk of relapse and a poorer leukemia-free survival. Severe cGVHD was associated with an increased risk of non-relapse mortality. Thus, real-world data suggest that preemptive IFN-α is effective for treating patients with AML with MRD after allo-HSCT.